EKSISTENSI PARIWISATA BUDAYA BALI DALAM KONSEP TRI HITAKARANA - I Gusti Agung Made Gede Mudana (Jurnal Ilmiah Hospitality Management, 2018)
The success of Bali tourism has become a legend both nationally and internationally. Bali Island is known as one of the best tourist islands in the world. Various awards were obtained by Bali Island as the best island and the most favorite place to travel throughout the world. Bali is the "best exotic destination". Tourism development by maintaining and empowering local communities is expected to be expected to provide welfare in the form of positive impacts in the economic, social, cultural and environmental fields. the fact that has been developed is cultural tourism. Cultural tourism is a type of pariwista which in its development uses regional culture which is imbued by Hindu religion, which is a national culture as the basic potential of national culture. The existence of tourism in Bali is expected to build intelligent, dignified and capable human resources based on the Tri Hita Karana concept, namely, the three causes of happiness and welfare factors. Therefore, the development of tourism in Bali by empowering local communities as a source of strength for the development of community-based cultural tourism and sustainability. Keywords: Cultural Tourism, Tri Hita KaranaÂ